EVALUASI KINERJA RUAS JALAN DAN SIMPANG TIDAK BERSINYAL DENGAN FASILITAS PUTAR BALIK (U-TURN) STUDI KASUS JALAN SRIWIJAYA DI KOTA MATARAM - ROHANI ROHANI; HASYIM HASYIM; MUHAMAD DILAN HIDAYTULLAH (Universitas Mahasaraswati K. Mataram, 2022)
Along with the increasing population and increasing development in all sectors in Mataram City every year, resulting in an increase in the volume of vehicles which often causes potential traffic conflicts. This condition results in disturbances for motorists in the flow of vehicles on the u-turn facility so that it affects performance on the road. One of the roads in the city of Mataram that is the choice in the travel route for the community is Jalan Sriwijaya. It is necessary to review the performance of roads with median openings, especially on unsignalized roads and intersections.The method used in this study is the calculation of urban road performance using MKJI 1997. Data from the location of median openings on unsignaled roads and intersections were collected through a field survey and then calculated the average traffic flow, average speed, average turning time average, capacity, degree of saturation, and level of road service. The results of the analysis show that the average traffic flow that occurs on the Sriwijaya road is 864.73 pcu/hour with a capacity of 2737.15 pcu/hour and the degree of saturation (DS) is 0.316 so that it is classified as a service level